Study of progesterone-induced blocking factor in the treatment of women with threatening abortion, taking into account the polymorphism of the progesterone receptor gene. - O. S. Kryvopustov (Medičnì Perspektivi)
Actual medical and social problem of modern obstetrics is threatening abortion. In its treatment, analogues of progesterone are used. Activation of progesterone receptors induces the production of anti-abortive protein-progesterone-induced blocking factor (PIBF). The dynamics of PIBF in 28 patients with the diagnosis of threatening abortion was analyzed. Women were treated by natural micronized progesterone depending on the features of the clinical course and single nucleotide polymorphism of the progesterone receptor gene rs590688. The quantitative content of PIBF in urine in pregnant women with threatening abortion was determined, namely, the increase in the content of this factor is associated with the prolongation of pregnancy. At the time of initiation of therapy, the concentration of PIBP was 28.8±1.5 (95% CI 26.7-29.2) ng/ml, and on the 7th day of therapy its concentration was 29.4±0.1 (95% CI 29.2-29.5) ng/ml. The increase in PIBF has reached a degree of statistical significance (T-W=15.0, p<0.001). In 27 (96.4%) patients who were pregnant, PIBP levels increased, 1 (3.6%) patient had spontaneous miscarriage on the 9th day of treatment. She had a decrease in concentration of PIBF in urine from 29.18 ng/ml at the time of admission to the hospital to 28.58 ng/ml on the 7th day of therapy. The study of progesterone-induced-blocking factor can be considered as an additional laboratory method of controlling progesterone therapy in women with threatening abortion in specialized research institutions.